Significados y tendencias del federalismo y de las relaciones intergubernamentales en Brasil y en España - Vasconcelos Rocha, Carlos (El Colegio de México A.C., 2014)
This paper compares the Spanish Autonomous model with the Brazilian Federative model. The characteristics of the two systems are set out with an evaluation of the real center-constraining capacity of their institutions, taking into account both the scale of the institutional structure and the scale of the political process. The intention is to evaluate how well-suited the institutions and political processes are to the requirements commonly considered necessary to the make-up of a federation. In the case of Spain, inter-governmental relations are less defined by a given institutional structure than by a political process of a highly centrifugal character, based on social characteristics divided into multiple ethnic and cultural identities. In the case of Brazil, the territorial distribution of power is better balanced, partly because it has a more solid underlying national identity.